Effectiveness of Flipped Classroom Model with Instagram in Junior High School - Istighfarin, Mega Amartya; Agustina, Lina (Universitas Muhammadiyah Surakarta, 2023)
Science learning is still something that students avoid because it requires perseverance, seriousness, and many experiments. This problem can be overcome using interactive learning media and following the independent curriculum. However, learning media must align with technological developments in this digital era. Therefore, with the flipped classroom learning model, one uses Instagram social media as a science learning medium. This study aimed to determine the effectiveness of flipped classroom learning with Instagram media on ecology and biodiversity class VII material in one of the junior high schools in Klaten Regency. This quantitative experimental study uses the N-Gain Score test with a one-group pretest-posttest design to measure the improvement of cognitive learning outcomes before and after. The results showed that the application of flipped classroom learning assisted by Instagram media on ecology and biodiversity material on student learning outcomes was included in the practical category with an interpretation of the N-Gain value of 0.77.